Testing Data for Consistency with Revealed Preference - Gross, John (The Review of Economics and Statistics, 1995)
The author develops a method of hypothesis testing for revealed preference tests. This method is particularly well suited to tests of commonality of tastes or tests of preference stability. He devises a metric based on an estimate of the fraction of expenditure wasted in maximizing utility if all consumers in the sample share the same utility function. This metric increases in size with increases in the proportion of observations having different tastes and with increasing differences in tastes. The author proposes bootstrap methods for estimating the distribution of the test statistic. Copyright 1995 by MIT Press.